2016
DOI: 10.1111/pala.12230
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared characterization of the Middle Devonian non‐vascular plant Spongiophyton

Abstract: Spectroscopy information (functional groups and semiquantitative data) by Fourier transform infrared (FTIR) spectroscopy of Spongiophyton Kr€ ausel emend. Chaloner et al. is reported for the first time, in an attempt to identify spectroscopic patterns that would differentiate species of these taxa. A total of 33 specimens identified as S. lenticularis, S. nanum and S. minutissimum and preserved as compressions were analysed. They come from the same fossiliferous horizon of one outcrop situated in the uppermost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Recent studies showed that biomolecules may be very well preserved in fossil leaves (Pšenička et al, 2005;Matsumura et al, 2016;Vajda et al, 2017Vajda et al, , 2021Lafuente Diaz et al, 2020. This preservation has proven true for plant cuticles as old as 360 Ma: these extremely wellpreserved cuticles were analyzed for their chemical composition and stability under the fossilization process (Lyons et al, 1995;Vajda et al, 2017), being also used for extensive phylogenetic studies using Fourier-transform infrared spectroscopy (FTIR) (Zodrow and Mastalerz, 2001;D'angelo, 2006;D'Angelo and Zodrow, 2015;Vajda et al, 2017Vajda et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that biomolecules may be very well preserved in fossil leaves (Pšenička et al, 2005;Matsumura et al, 2016;Vajda et al, 2017Vajda et al, , 2021Lafuente Diaz et al, 2020. This preservation has proven true for plant cuticles as old as 360 Ma: these extremely wellpreserved cuticles were analyzed for their chemical composition and stability under the fossilization process (Lyons et al, 1995;Vajda et al, 2017), being also used for extensive phylogenetic studies using Fourier-transform infrared spectroscopy (FTIR) (Zodrow and Mastalerz, 2001;D'angelo, 2006;D'Angelo and Zodrow, 2015;Vajda et al, 2017Vajda et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used palynological and palaeobotanical processing methods include cleaning steps using: HCl and/or HF (e.g., Steemans et al, 2010;Matsumura et al, 2016;Lafuente Diaz et al, 2020;Jardine et al, 2021) for inorganics removal; and for cuticle or coal maceration, Schulze's solution (Zodrow and Mastalerz, 2009;D'Angelo et al, 2011;Zodrow et al, 2012;Jardine et al, 2021), followed by KOH (Pšenička et al, 2005;Slodownik et al, 2021). Yet, potential alterations of the fossil chemical composition caused by the different cleaning reagents used are not fully understood, as these protocols were developed and became standard practice before chemical spectroscopic studies of fossil cuticles and pollen became popular.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the preservation types and paleochemotaxonomy of plant fossil remains as well as paleoenvironmental, diagenetic, and postdiagenetic conditions involved in fossilization processes have been mainly analyzed (e.g., D'Angelo and Zodrow, 2015;Zodrow et al, 2016;Lafuente Diaz et al, 2018a, 2019a, 2020aZodrow and Mastalerz, 2019, among others). These investigations have been predominantly carried out on Pennsylvanian gymnosperms, vegetative and reproductive organs from the Sydney Coalfield, Canada and, to a lesser extent, on plant remains from the Devonian, Carboniferous, and Triassic of Canada, the Czech Republic, Spain, and Brazil, among others (e.g., Pšenicka et al, 2005;D'Angelo and Zodrow, 2015;Matsumura et al, 2016). Among the latest analyzes, a chemical representation of the fertile structures of Trigonocarpus grandis in organic connection to vegetative organs has been obtained (Zodrow et al, 2013).…”
mentioning
confidence: 99%